Transfers to Households with Children and Child Development. (7th December 2016) - Del Boca, Daniela; Flinn, Christopher; Wiswall, Matthew
Abstract : We utilise a model of household investments in the development of children to explore the impact of various transfer policies on the distribution of child outcomes. We develop a cost criterion that can be used to compare the efficacy of unrestricted, restricted, and conditional cash transfer (CCT) systems, and find that an optimally chosen CCT programme is the most cost‐efficient way to attain any given gain in average child quality. We explore several design elements for the CCT system and discuss the role of production function uncertainty and measurement error.